Boas práticas para tornar ambientalmente sustentável a operação de armazéns - Gois, Larissa Emerick (2019)
The objective of this dissertation is to define a set of good practices for the operation of warehouses in order to improve their environmental sustainability. It is also hoped to evaluate the impacts generated from the adoption of such good practices. For this, a normative bibliographic review will be carried out with a case study. The limitations were initially found in the literature regarding the green warehouse, a subject that has not yet been approached in relation to its management and operation. The originality of the work is related to the elaboration of good practices for operation and warehouse management whose focus is to improve the results of environmental sustainability resulting from the movement of products in stock, improving the use of energy and the resulting emissions of greenhouse gases (GHG) and air pollutants.